2007
DOI: 10.3200/jmbr.39.4.276-290
|View full text |Cite
|
Sign up to set email alerts
|

Adjustments to Local Friction in Multifinger Prehension

Abstract: The authors studied the effects of surface friction at the digit-object interface on digit forces and moments when 12 participants statically held an object in a 5-digit grasp. The authors changed lowfriction contact (LFC) with rayon and high-friction contact (HFC) with sandpaper independently for each digit in all 32 possible combinations. Normal forces of the thumb and virtual finger (VF), an imagined finger with a mechanical effect equal to that of the 4 fingers, increased with the thumb at LFC or with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
(63 reference statements)
2
23
0
Order By: Relevance
“…Local and non-local responses have been examined in some earlier studies during submaximal grip force tasks in healthy hands. Aoki et al (2007) investigated the role of tactile information in adapting grip object properties, and found that changes in texture at a given digit elicit force adjustments at the same as well as other digits, indicating that sensory information at one digit affects the force modulation at non-stimulated digits. Our current results further implied that individual sensory input is shared across all the digits and the disturbed signal from local sensory channel(s) has a more comprehensive impact on the process of the motor output execution in the sensorimotor integration.…”
Section: Discussionmentioning
confidence: 99%
“…Local and non-local responses have been examined in some earlier studies during submaximal grip force tasks in healthy hands. Aoki et al (2007) investigated the role of tactile information in adapting grip object properties, and found that changes in texture at a given digit elicit force adjustments at the same as well as other digits, indicating that sensory information at one digit affects the force modulation at non-stimulated digits. Our current results further implied that individual sensory input is shared across all the digits and the disturbed signal from local sensory channel(s) has a more comprehensive impact on the process of the motor output execution in the sensorimotor integration.…”
Section: Discussionmentioning
confidence: 99%
“…Since the handle was not perfectly symmetrical and there was a residual digit moment (see Appendix A), changes in the normal forces could lead to violation of the handle orientation requirement, in particular because of the changes in the lever arms for the vertical tangential forces. Earlier studies have shown so-called chain effects (Gao et al 2005; Aoki et al 2007; Zatsiorsky and Latash 2008) when a change in only a subset of digit forces and/or other features of the task (such as handle geometry and friction conditions) lead to changes in many other variables caused by the static constraints.…”
Section: Discussionmentioning
confidence: 99%
“…an effect of friction at a given digit on the force exerted by this digit. The term synergic refers to changes in a finger's force in response to changes in friction under other finger(s) (Aoki et al 2006(Aoki et al , 2007Zatsiorsky et al 2006). An example of the local and synergic reactions could be seen in experiments in which the friction under each digit was different, either high or low, resulting in eight friction conditions (for the three-digit grasps, Niu et al 2007) or 32 friction conditions (Aoki et al 2007).…”
Section: Local and Synergic Reactions To Perturbationsmentioning
confidence: 99%
“…For instance, to keep the total tangential force constant, the tangential forces of the thumb and fingers changed in opposite directions (Figure 10). Not only the VF tangential force but also the tangential forces of the individual fingers are affected by the local friction conditions (Aoki et al 2007;Niu et al 2007). The tangential force adjustments to the local friction support the notion that the VF tangential force sharing is under neural control; the sharing percentage is not determined solely by the passive mechanical properties of the individual fingers and joints.…”
Section: Local and Synergic Reactions To Perturbationsmentioning
confidence: 99%